Research on the Innovation of the New Model for the Cultivation of Government Accounting Professionals under the "Accrual Basis of Big Data Analysis of Government Comprehensive Financial Report. Issue 4 (February 2021) - Hua, Yuhuan; Shang, Desheng
Abstract: The development of government financial report in the era of big data is undergoing a severe change. Government financial report is undergoing a change from post-reporting to pre-reporting, and post-reporting accounting information data to providing the government with a forecast of the future. To improve the accrual basis for compiling government comprehensive financial reports under the condition of big data, it is necessary to promote the healthy development of graduate education of accounting major, study the reform measures of government accounting textbook system, and strengthen the vocational skills training of government accountants. It is an important content in the accrual accounting reform to establish a new mode of government accounting personnel training.